(untitled) (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the influence of exports and imports on the trade balance in North Sumatra Province during the 2020–2025 period. The research employs a quantitative approach using secondary data obtained from the Central Statistics Agency (BPS). The variables used in this study consist of exports as the first independent variable (X1), imports as the second independent variable (X2), and the trade balance as the dependent variable (Y). Data analysis techniques include descriptive analysis to describe the development of export, import, and trade balance values, as well as analysis of the relationship between variables to determine the influence of independent variables on the dependent variable. The results indicate that exports have a positive effect on the trade balance, an increase in export value tends to increase the trade surplus. Conversely, an increase in imports tends to reduce the trade surplus due to higher expenditures on foreign goods. These findings indicate that international trade dynamics play a significant role in determining regional trade balance conditions. Therefore, economic policies that encourage export growth and optimize import management are necessary to maintain the stability of the trade balance in North Sumatra Province.